Optimizing surgical outcomes through preoperative parathyroid localization - Pal, Banyeswar; Jha, Hem Narayan (International Journal of Research in Medical Sciences, 2025)
Preoperative parathyroid localization is pivotal in ensuring surgical precision and optimizing outcomes in patients with parathyroid disorders. Advances in imaging techniques have significantly enhanced diagnostic accuracy and reduced complications. A systematic search strategy was designed to identify relevant literature published between June 2014 and September 2024. Databases including PubMed, Scopus, and Google Scholar were utilized, using search terms such as "preoperative localization," "parathyroid imaging," "parathyroidectomy outcomes," "ultrasonography," "SPECT," and "4D-CT." Inclusion criteria encompassed studies focusing on preoperative imaging modalities for parathyroid localization, those evaluating surgical outcomes, and original research articles in English. The qualitative synthesis emphasized patterns in imaging efficacy and surgical outcomes across different studies. Among the imaging techniques, 4D-CT demonstrated the highest localization accuracy (95%), followed by SPECT (89%) and ultrasonography (80%). Patients with precise preoperative localization experienced shorter operative times, fewer complications, and higher rates of surgical success compared to those without effective localization. Integrating advanced imaging modalities into preoperative planning significantly improves surgical precision and outcomes in parathyroid surgery. These findings advocate for their routine use in clinical practice to enhance patient care.